Dose-response relation between serum total cholesterol levels and overall cancer risk: evidence from 12 prospective studies involving 1, 926, 275 participants. (19th May 2019) - Wu, Bing; Teng, Li; He, Du; Yu, Dong-Dong; Jiang, Fan
Abstract: This study aimed to clarify the association between serum total cholesterol (TC) levels and overall cancer risk. Study-specific relative risks (RR) and 95% confidence intervals (CI) were pooled using a random-effects model, and dose–response relation was also evaluated. Twelve prospective studies were identified with a total of 1, 926, 275 participants and 13, 1676 cases. High levels of serum TC showed an inverse association with overall cancer risk (RR for the highest versus the lowest category: 0.87, 95% CI: 0.83 ∼ 0.90; I 2  = 52.5%). A linear dose-response relation between serum TC levels and overall cancer risk was found ( p  = .004 for Wald test; I 2  = 49.6%), and the pooled RR was 0.92 (95% CI: 0.89 ∼ 0.94) for 3 mmol/L, 0.86 (95% CI: 0.81 ∼ 0.90) for 5 mmol/L, 0.80 (95% CI: 0.74 ∼ 0.87) for 7 mmol/L. Our dose-response meta-analysis of 12 prospective studies indicated that higher serum TC levels were significantly associated with reduced cancer risk.